1996
DOI: 10.1016/s0022-5347(01)66349-3
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Testicular Volume: Comparison of 3 Different Methods

Abstract: To measure testicular size use of an ordinary ruler is recommended for clinical purposes because of its simplicity, availability and low cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 7 publications
4
43
1
1
Order By: Relevance
“…However, some studies showed that the different methods to measure testicular size in clinical practice are well comparable and none is superior to any other [13,14]. Since the goal of this study was the comparison of three physicians' measurements of testicular volume, we did not compare the results of Prader orchidometer measurements with any other methods including ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies showed that the different methods to measure testicular size in clinical practice are well comparable and none is superior to any other [13,14]. Since the goal of this study was the comparison of three physicians' measurements of testicular volume, we did not compare the results of Prader orchidometer measurements with any other methods including ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…We used the Lambert formula (0.71  length  width  depth) to calculate the testicular volume from ultrasound data, with volume values between 15 and 30 ml as reference. 27 Selected patients received testicular biopsy. We diagnosed testicular disease in the presence of isolated impaired spermatogenesis (serum levels of follicle-stimulating hormone 48 U/l but normal luteinizing hormone and testosterone levels) or subclinical (compensated) hypogonadism (total serum testosterone concentration 43.1 ng/ml and luteinizing hormone X9.4 U/l) or hypogonadism (total serum testosterone concentration below 2.3 ng/ml, or between 2.3 and 3.5 ng/ml with free testosterone values p65 pg/ml).…”
Section: Clinical Studymentioning
confidence: 99%
“…Measurements of testicular length, width, and height were obtained by using electronic callipers. The figures obtained were then substituted into the formula of a prolate ellipsoid to estimate the testicular volume [Vol (ml) = 0.523 9 L 9 W 9 H] [9, [16][17][18][19][20][21].…”
Section: Techniquementioning
confidence: 99%